Sex differentials in the prevalence of behavioral risk factors and non-communicable diseases in adult populations of West Kazakhstan - Baspakova, Akmaral; Abitova, Anara Zh.; Mussin, Nadiar M.; Kaliyev, Asset A.; Yerimbetova, Gulmira; Zhumagaliyeva, Saltanat; Ashimova, Zhanat; Zhilisbayeva, Kulyash R.; Umbetova, Aigerim A.; Nurtazina, Alma U.; Tamadon, Amin (Frontiers in Public Health, 2024)
The prevalence of non–communicable diseases (NCDs) are increasing worldwide. Several modifiable risk factors, such as smoking, alcohol drinking, physical inactivity, and obesity, have been linked to the development of NCDs in both genders. Understanding the prevalence of these risk factors and their associated factors is crucial for effective intervention planning in adult populations. This study aimed to provide an overview of the prevalence and associated factors of these risk behaviors among different genders adults in West Kazakhstan. A cross–sectional study was conducted in four regions of West Kazakhstan. A stratified multistage sampling technique was utilized to obtain a representative sample size of 4800 participants aged 18 to 69 years. Trained researchers administered face–to–face interviews using validated questionnaires to gather information pertaining to sociodemographic characteristics, smoking habits, alcohol drinking, dietary patterns, physical activity levels, body mass index (BMI), and prevalent diseases. This study, which included 4800 participants in West Kazakhstan, revealed some striking numerical findings. The overall prevalence rates of behavioral risk factors and metabolic conditions were as follows: smoking 13.6% (95%CI 3.2–24.0%), alcohol drinking 47.0% (27.7–66.3%), current obesity 22.3% (9.0–35.6%) and physical inactivity 80.7% (55.4–106.0%). In addition, the overall prevalence rates of metabolic conditions were hypertension 25.6% (11.3–39.9%), diabetes 7.5% (0.2–15.2%), high cholesterol 11.8% (2.1–21.5%), and cardiovascular diseases 13.0% (2.8–23.2%). Additionally, a higher prevalence of high cholesterol was observed in men, and a greater prevalence of heart disease was identified in women. Multinomial logistic regression revealed that physical inactivity was associated with hypertension, diabetes, and heart disease, while obesity was linked to hypertension, high cholesterol, and heart disease. This study in West Kazakhstan identified variations in the prevalence of behavioral risk factors and NCDs, highlighting gender, age, and regional disparities. Notably, men showed higher rates of smoking and alcohol drinking, while women had a greater prevalence of physical inactivity and obesity. Gender and regional differences were evident, with the West Kazakhstan region standing out for distinct patterns. Tailored interventions are crucial to address these disparities and enhance public health in the region.